The nexus between substance abuse and commercial sex work in Musina boarder town, Limpopo Province, South Africa - Svinurai, A; Makhubele, J. C (Gender and behaviour, 2018)
Substance abuse and sex work share an intrinsic relationship, with the debate, its cause and effect difficult to ascertain. Substance abuse behaviours is a common phenomenon among sex workers the world over, with researches unravelling high prevalence of substance abuse in this population. In developed countries, there is general consensus amongst researchers that substance abuse especially on hard substances result in sex work. A substance abuser engages in sex work as an avenue to sustain his/her substance abusing behaviour. In Africa, however, the relationship of the two is not clear, and this paper sought to appraise the nexus between substance abuse and sex work in the busiest border town in Southern Africa, Musina Border Post Town. The research was qualitative in approach, and explorative in design with ten participants interviewed. Mostly, sex workers start abusing substances on and after entry into sex work. Substances are used to boost confidence to approach clients, to copy with intra and inter personal issues in sex trade and sex workers feel compelled when offered substances by clients and potential clients. Sex work in Africa is mainly for survival, with the conditions of service trapping sex workers to substance abuse. The shared environments of sex trade and substance abuse make sex workers vulnerable to substance abuse. It is important that the environment upon which sex workers operate is made conducive in order to limit the trapping factors of substance abuse in sex work
Article published in the Gender and behaviour 16(3), 2018, 12152 - 12166
Keywords: Substance Abuse; Commercial Sex Work; Border post; Prostitutes; Substance abuse--Africa, Sub Saharan